2020
DOI: 10.1155/2020/8274193
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Screening and Identification of Phillyrin Metabolites in Rats Based on UHPLC-Q-Exactive Mass Spectrometry Combined with Multi-Channel Data Mining

Abstract: Phillyrin, a well-known bisepoxylignan, has been shown to have many critical pharmacological activities. In this study, a novel strategy for the extensive acquisition and use of data was established based on UHPLC-Q-Exactive mass spectrometry to analyze and identify the in vivo metabolites of phillyrin and to elucidate the in vivo metabolic pathways of phillyrin. Among them, the generation of data sets was mainly due to multichannel data mining methods, such as high extracted ion chromatogram (HEIC), diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Thus, unique metabolites of different species may be formed during adaptation to growing conditions. Previous studies have isolated and identified various medically active compounds in the fruits of Forsythia suspensa , including the structures of rengyosides A, B and C [ 11 ]. Numerous fruit-derived metabolites have been isolated from previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, unique metabolites of different species may be formed during adaptation to growing conditions. Previous studies have isolated and identified various medically active compounds in the fruits of Forsythia suspensa , including the structures of rengyosides A, B and C [ 11 ]. Numerous fruit-derived metabolites have been isolated from previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Phillyrin, a natural lignan, is the main bioactive component of F. suspensa . Studies on phillyrin have shown that it is found mainly in the leaves and fruits of the plant F. suspensa (Kim et al, 2000; Xia et al, 2011): phillyrin can be extracted by maceration, Soxhlet, and microwave‐assisted extraction methods (Ma et al, 2020; Xu et al, 2019). Relevant reports indicated no acute toxicity of water or ethanol extract of the leaves of F. suspensa in mice, even at daily dose of 61.60 g/kg (Ai et al, 2011; Hou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%